Ethanol fermentation from raw starch of sweet sorghum grains - Nadir, Najiah; Mel, Maizirwan; Abd Karim, Mohd Ismail (2010)
Ethanol can be readily produced by fermentation of simple sugars that are converted from either starchy crops or cellulosic materials. The hydrolysis and fermentation were used to produce ethanol from raw starch of sweet sorghum grains by utilizing commercially available α-amylase and glucoamylase. Ethanol production from hydrolyzed sweet sorghum was analyzed under different fermentation conditions using Saccharomyces cerevisiae in batch fermentation. The concentration of inoculum, urea, NPK (nitrogen, phosphorus, and potassium), temperature, initial pH, and agitation were investigated simultaneously through two-level factorial design. The maximum ethanol concentration (66.70 g/L) were obtained at concentration of inoculum of 0.3% (w/w), urea of 0.60% (w/w), NPK of 0.05% (w/w), temperature of 30°C, initial pH of 6.0, and agitation of 100 rpm. As shown in the analysis of variance (ANOVA) result, the concentration of inoculum, urea, initial pH, and agitation have contributed more significant effect on fermentation of hydrolyzed sweet sorghum. The major factors for fermentation were optimized by the central composite design (CCD) under the response surface method (RSM). After further optimization using CCD, the optimum fermentation conditions for maximum ethanol production of 75.48 g/L were predicted at 0.43% (w/w) of inoculum concentration, 5.62 of initial pH of fermentation media, and 50 rpm of agitation speed.